Side Effect, Husband Support and Level of Knowledge on the Incidence of Contraceptive Acceptors Dropout - Boimau, Adriana M.S; Boimau, Serlyansie V.; Kambuno, Norma Tiku (JURNAL INFO KESEHATAN, 2023)
Family planning program is an effort made by the Indonesian government to decrease the birth rate and control the population. The succuss of family planning program in decreasing the birth rate is influenced by several factors, including the incidence of dropout (DO) regarding the use of contraceptive methods. The high contraceptive acceptors DO rate indicates a problem regarding the use of contraceptive methods. DO cases in Kupang Regency, East Nusa Tenggara (NTT) Province, increased from 1.1% in 2018 to 9.1% in 2021. Therefore, it is necessary to study the factors that cause the increase in the incidence of Contraceptive Acceptors DO. This study aims to determine the factors related to the incidence of Contraceptive Acceptors DO in East Penfui Village, the work area of Tarus Community Health Center, Kupang Regency. This was an analytical survey study with cross-sectional approach. The population involved was family planning acceptors in the village from March to October 2020, as many as 163 acceptors. The samples of 69 acceptors were selected using simple random sampling technique. Data were collected through interviews and documentation. Data were analyzed using Chi-square test. The results revealed that there were three factors which influenced the incidence of contraceptive acceptors DO, namely maternal level of knowledge (p=0.006, husband support for his wife (p=0.003), and side effects regarding contraceptive methods (p=0.014). It can be concluded that a personal approach was needed. Counseling on the side effects of contraception and door to door education can be solutions to be performed by CHC officers as well as existing health cadres.